Legal Protection for People with Mental Disorders According to the Welfare Concept of the Indonesian State - Neneng Salama; CSA TEDDY LESMANA, SH MH (Westscience Press, 2023)
This study aims to determine the extent of legal protection for people with mental disorders according to the Indonesian state welfare concept. Legal protection is an effort to protect human rights which aims to protect the interests of every citizen in a form of service that must be provided by the government to its citizens to provide a sense of security and peace to every citizen of society. As regulated under the 1945 Constitution of the Republic of Indonesia, the state's responsibility for the protection of human rights is a very important matter. As described in Article 28I Paragraph (4) which reads: